1988
DOI: 10.1177/009164718801600205
|View full text |Cite
|
Sign up to set email alerts
|

Hope and its Relationship to Spiritual Well-Being

Abstract: Hope is essential to physical and psychosocial well-being and plays a central role in one's ability to deal with illness and suffering. It's relationship to spiritual well-being, however, has not been explored empirically. This article addresses the conceptual similarities of hope and spiritual well-being and reports the results of a correlational study examining the relationship in a sample of healthy individuals. While hope was found to be related to both the religious and existential dimensions of spiritual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…Psychosomatic medicine has long recognized that emotions such as laughter, love, and hope have a positive effect on the healing process (Carson, Soeken, & Grimm, 1988;Richardson, 2000). Cancer studies have consistently demonstrated that hope is an essential element in the coping process (Mytko & Knight, 1999;Rustøen, 1995).…”
Section: Hopementioning
confidence: 99%
See 2 more Smart Citations
“…Psychosomatic medicine has long recognized that emotions such as laughter, love, and hope have a positive effect on the healing process (Carson, Soeken, & Grimm, 1988;Richardson, 2000). Cancer studies have consistently demonstrated that hope is an essential element in the coping process (Mytko & Knight, 1999;Rustøen, 1995).…”
Section: Hopementioning
confidence: 99%
“…Research has shown the importance of belief and hope in the areas of physical and mental health (Nekolaichuk, Jevne, & Maguire 1999;Gall & Cornblat, 2002). Multidisciplinary writers such as theologians, health care providers, and philosophers have proposed that hope consists of four major themes: future orientation, goal setting, action, and relationships and is an effective coping mechanism for dealing with illness and suffering (Carson et al, 1988). All four themes need to be operating concurrently to aid individuals to cope with and transform their experience with illness.…”
Section: Hopementioning
confidence: 99%
See 1 more Smart Citation
“…An article by Carson, Soeken, and Grimm (1988) related hope to .spiritual well-being, existential well-being, and religious well-be-Downloaded by [UQ Library] at 16:13 20 November 2014 ing. "Responses showed that both trait and state hope are positively related to spiritual well-being, existential well-being, and religious well-being."…”
Section: Religiosity and Well-beingmentioning
confidence: 99%
“…Over several studies, using Paloutzian and Ellison's ( 1982) spiritual well-being scale, religious well-being has been correlated with a variety of other variables. For example, religious well-being has been positively correlated with hardiness, a concept defined by Kobasa ( 1979) to include challenge, commitment, and control (Carson & Green, 1992), and hope (Carson et al, 1988;Carson et al, 1990;Mickley et al, 1992); and negatively correlated with depression (Fehring et al, 1987) and loneliness (Miller, 1985;Paloutzian & Ellison, 1982) in samples of both ill and well adults.…”
Section: Impact On Mental Healthmentioning
confidence: 99%